A Simultaneous Equations Model of Coffee Brand Pricing and Advertising - Nelson, Philip; Siegfried, John; Howell, John (The Review of Economics and Statistics, 1992)
This paper explores the relationship between a differentiated brand's market share and its price in the context of a model that recognizes the endogeneity of the brand's advertising behavior and pricing decisions. The empirical analysis suggests that General Foods charged higher prices for its regular-grind Maxwell House coffee in geographic areas where the brand's market share was relatively large. Available cross-sectional, time-series data and company documents suggest that this empirical relationship is attributable to the preference grocery retailers have for putting dominant coffee brands on special, rather than cross-sectional variations in costs, market concentration, or consumer tastes. Copyright 1992 by MIT Press.